STUDI MEKANISME INTERAKSI GLIKLAZID-SIPROFLOKSASIN PADA TRANSPORTER P- GLYCOPROTEIN DENGAN PEMBERIAN KINIDIN PADA TIKUS WISTAR JANTAN - Adani Djuli, Azalea
Patients with type II Diabetes Mellitus along with complications such as urinary tract infection are usually treated by a combination of gliclazide and ciprofloxacin as therapy. Previous study showed that the interaction between gliclazide and ciprofloxacin caused ð?íðð?ð???» ®ð???»??? ®ð??? elimination. It was assumed that the interaction involving P-glycoprotein (P-gp). This current research was aimed to study the role of P-gp in the interaction between gliclazide and ciprofloxacin using quinidine as a widely accepted P-gp inhibitor. Male wistar rats were divided into four groups (n=5). Group I and II were given gliclazide and ciprofloxacin, respectively, while group III and IV were given gliclazide and ciprofloxacin, respectively along with intravenous infusion of quinidine. Blood samples were collected via femoral artery at pre-determined sampling points. Samples were analyzed by HPLC and the pharmacokinetic parameters were defined. Plasma concentrations of quinidine were determined to evaluate with the target concentration. Pharmacokinetic parameters of gliclazide in group III showed a significant difference only in the tmax (1.50 ± 0.00 to 0.55 ± 0.11 h) compared to group I. While pharmacokinetic parameters of ciprofloxacin in group IV differed from ã????==??í??ð?ã   ?ðã?ð»ð® ??¸±®?± ?± ????????ð???0.24 ± 0.03 to 0.07 ± 0.01 /h), clearance (16.67 ± 3.89 to 9.44 ± 1.51 l/kg.h), tmax (0.75 ± 0.00 to 0.50 ± 0.00), also a significant increase (p<0.05) in biological half life (2.97 ± 0.45 to 9.98 ± 1.34 h). Administration of gliclazide along with quinidine did not cause any difference in its elimination parameters. While administration of ciprofloxacin along with quinidine caused a significant decrease in elimination of ciprofloxacin indicated that ciprofloxacin was a substrate of P-gp.